Mechanical Signature of Red Blood Cells Flowing Out of a Microfluidic Constriction Is Impacted by Membrane Elasticity, Cell Surface-to-Volume Ratio and Diseases - Faivre, Magalie; Renoux, Céline; Bessaa, Amel; Da Costa, Lydie; Joly, Philippe; Gauthier, Alexandra; Connes, Philippe (Frontiers in Physiology, 2020)
Despite the fact that Red Blood Cells (RBCs) have been intensively studied in the past fifty years to characterize mechanical phenotypes associated with both healthy and pathological states, only ektacytometry (i.e. laser diffractometry) is currently used by hematologists to screen for RBC membrane disorders. Therefore, the development of new diagnostic tools able to perform analysis at the scale of a single cell, over a statistically relevant population, would provide important complementary informations. But these new diagnostic tools would have to be able to discriminate between different disorders causing a change in RBCs mechanical properties. We evaluted the mechanical response of artificially rigidified RBCs flowing through a microfluidic constriction. The geometry consists in a 50 µm wide channel with a succession of 14 tooth-like patterns, each composed of a 5 µm wide and 10 µm long constriction, associated with a 25 µm wide and 10 µm long enlargement. RBCs deformability was altered using two chemical treatments, known to affect RBCs membrane surface area and membrane deformability, lysolecithine (LPC) and diamide, respectively. Differences between samples were highlighted by the representation of the inverse of the shape recovery time (1/tau_r), versus the extension at the exit of the constriction, Dout. The results demonstrate that our approach is able to provide a direct signature of RBCs membrane composition and architecture, as it allows discriminating the effect of changes in RBCs membrane surface area from changes in RBCs membrane deformability. Finally, in order to evaluate the potential of our microsystem to detect pathological cells, we have performed preliminary experiments on patients with Hereditary Spherocytosis or Sickle Cell Anemia.